The power of seeing in problem solving and creativity: an issue under discussion - Vale, Isabel (2018)
The teaching of mathematics is a complex task, as there are several aspects that must be considered simultaneously, which requires that teachers have knowledge and deep understanding of the issues and mathematical content they expect to teach and also requires that teachers have a good understanding of how to teach, in order to be effective in the development of mathematics learning of all students.